Descriptive Study on Kindergarten Teachers' Perceptions of the Implementation of STEAM-Based Merdeka Curriculum in Kindergarten Education in West Java Province Region - Sunanih, Sunanih; Maulidah, Neni; Sunhaji,; Mutijah,; Abdul Rahim, Mohd Hisyam (Advances in Humanities and Contemporary Studies, 2024)
This article aims to describe kindergarten teachers' perceptions on the implementation of Merdeka Curriculum based on STEAM in kindergarten education in West Java Province. A quantitative descriptive study was conducted with 44 respondents from 44 kindergartens in the province. The participants, who had been teaching for between one and 30 years, were all kindergarten teachers. The research sample was identified through purposive sampling, following the minimum number of research participants required for descriptive research. Data were gathered through questionnaires to provide a description. Teachers' views on Merdeka Curriculum with focus on STEAM include (1) insights on its implementation in early childhood education and (2) perspectives on integrating Science, Technology, Engineering, Arts, and Mathematics (STEAM) in early childhood education. (3) The main benefits of implementing the Merdeka Curriculum based on STEAM in kindergarten, and (4) the primary challenge in implementing the Merdeka Curriculum based on STEAM in kindergarten, as perceived objectively.